2008
DOI: 10.1002/ijc.23775
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fat4 as a candidate tumor suppressor gene in breast cancers

Abstract: Fat, a candidate tumor suppressor in Drosophila, is a component of Hippo signaling pathway involved in controlling organ size. We found that a ∼3 Mbp deletion in mouse chromosome 3 caused tumorigenesis of a non‐tumorigenic mammary epithelial cell line. The expression of Fat4 gene, one member of the Fat family, in the deleted region was inactivated, which resulted from promoter methylation of another Fat4 allele following the deletion of one Fat4 allele. Re‐expression of Fat4 in Fat4‐deficient tumor cells suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 33 publications
7
93
0
Order By: Relevance
“…Yorkie) of lats have been identified, which constitute a novel signaling pathway called Hippo-LATS pathway that plays important roles in organ size control by regulation of cell proliferation [22][23][24][25][26][27][28][29][30]. Most of the mammalian homologs of the components of the Drosophila Hippo-LATS pathway have been identified (Fat4 for Fat; Merlin for Merlin, FRMD6 for Expanded, MOB1 for MATS; Mst1/2 for Hippo, hWW45 for Salvador; LATS1/2 for lats; YAP or TAZ for Yorkie) [25,[31][32][33][34][35][36][37][38][39][40][41][42]. Most significantly, it has been shown that conditional knockdown of merlin, Mst1/2, or WW45 (Salvador), or overexpression of YAP in the liver results in increased liver size in mice [25,33,43,44], suggesting that the Hippo-LATS signaling pathway is an evolutionally conserved pathway regulating animal organ size by regulating cell numbers.…”
Section: The Role Of Cell Proliferation In Size Controlmentioning
confidence: 99%
“…Yorkie) of lats have been identified, which constitute a novel signaling pathway called Hippo-LATS pathway that plays important roles in organ size control by regulation of cell proliferation [22][23][24][25][26][27][28][29][30]. Most of the mammalian homologs of the components of the Drosophila Hippo-LATS pathway have been identified (Fat4 for Fat; Merlin for Merlin, FRMD6 for Expanded, MOB1 for MATS; Mst1/2 for Hippo, hWW45 for Salvador; LATS1/2 for lats; YAP or TAZ for Yorkie) [25,[31][32][33][34][35][36][37][38][39][40][41][42]. Most significantly, it has been shown that conditional knockdown of merlin, Mst1/2, or WW45 (Salvador), or overexpression of YAP in the liver results in increased liver size in mice [25,33,43,44], suggesting that the Hippo-LATS signaling pathway is an evolutionally conserved pathway regulating animal organ size by regulating cell numbers.…”
Section: The Role Of Cell Proliferation In Size Controlmentioning
confidence: 99%
“…Mutation of many of these genes has been implicated in human cancers (McClatchey and Giovannini, 2005;Harvey and Tapon, 2007;Yokoyama et al, 2008), Fat4/FatJ has recently been implicated as a breast tumour suppressor gene (Qi et al, 2009), and Yap1 expression and nuclear localisation is upregulated in Shh-associated medulloblastomas (Fernandez et al, 2009). Recent studies show that the Hippo pathway controls the number of neuronal progenitors in the neural tube by influencing cell proliferation and apoptosis (Cao et al, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…75 Furthermore, Fat4 is a candidate tumor suppressor whose expression is lost in a fraction of human breast tumor cell lines and primary tumors. 76 …”
Section: How Does the Hpo Pathway Read The Spatial And Temporal Signals?mentioning
confidence: 99%